Effect of Exercise Instructions With Ambulatory Accelerometer in Japanese Patients With Type 2 Diabetes: a Randomized Control Trial - Matsushita, Jin; Okada, Hiroshi; Okada, Yuki; Sekiyama, Takashi; Iida, Hideto; Shindo, Atsushi; Murata, Hiroaki; Fukui, Michiaki (Frontiers in Endocrinology, 2022)
This study aimed to investigate the effects of physical therapists’ exercise instructions in Japanese patients with type 2 diabetes. Thirty-six participants were recruited from the outpatient clinic at Matsushita Memorial Hospital, Osaka, Japan from June 2020 to September 2020 and were randomly assigned to either the non-intervention or intervention group. The intervention group received exercise instructions from physical therapists for 30 min at baseline (week 0) and at week 4 by referring to ambulatory accelerometer records. Laboratory parameters, physical activity, body composition, motor skill, and transtheoretical model were assessed in both the groups at baseline (week 0) and week 8. In week 8, patients in the intervention group had a statistically significant reduction in HbA1c levels compared with those in the non-intervention group (7.3% [6.8-%–7.9%] vs. 7.4% [7.3%–7.7%], P = 0.04). The number of steps per day (P = 0.001), energy expenditure (P = 0.01), lower extremity muscle strength (P = 0.002), and 6-min walk test results (P = 0.04) were significantly increased in the intervention group compared with those in the non-intervention group in week 8. The transtheoretical model varied between baseline (week 0) and week 8 only in the intervention group (P < 0.001). Thus, outpatient exercise instructions from physical therapists could improve glycemic control owing to physical activity by improving motor skills and changing the transtheoretical model in Japanese patients with type 2 diabetes.